Ageing Population: Comparative Analysis Among European Union States - Laura Diaconu (CES Working Papers, 2015)
The aging population is a global phenomenon, which has affected almost all the EU states. The consequences are very important since it affects the socio-economic environment usually on the long run. Some of them could consist in increasing the public expenditure on pensions, social security and health services, which will raise the overall burden on the working population. Sometimes, a significant reduction of the labour force will even diminish the growth rate of an economy. Considering these aspects, the present paper intends to analyse the demographic situation from the EU states, the factors that have generated it and to identify the possible future trends. To determine the evolution of the ageing population phenomenon, we have analysed some demographic indicators included in various statistical reports and databases, such as the fertility rate, the median age, the percentage of population over a certain age and the age dependency ratio.
Keywords: J1; J11; 330; ageing population; fertility rate; population pyramid; median age; age dependency ratio